What befell the slave-seekers [electronic resource] : a story of the Haidahs on Queen Charlotte's Island, B.C. - Deans, James, 1827-1905. ([S.l. : s.n., 1888)
Signed: James Deans. From: The Journal of American folk-lore, v. 1 no. 2, July-Sept. 1888. Caption title. Electronic reproduction. Mode of access: Internet. 44